Update in Noninvasive Home Mechanical Ventilation: A Narrative Review of Indications, Outcomes, and Monitoring - Laura Tregidgo; Prasheena Naran; Eshrina Gosal; Rebecca F. D’Cruz (Canadian Respiratory Journal)
Hypercapnic respiratory failure arises due to an imbalance in the load-capacity-drive relationship of the respiratory muscle pump, typically arising in patients with chronic obstructive pulmonary disease, obesity-related respiratory failure, and neuromuscular disease. Patients at risk of developing chronic respiratory failure and those with established disease should be referred to a specialist ventilation unit for evaluation and consideration of home noninvasive ventilation (NIV) initiation. Clinical trials demonstrate that, following careful patient selection, home NIV can improve a range of clinical, patient-reported, and physiological outcomes. This narrative review provides an overview of the pathophysiology of chronic respiratory failure, evidence-based applications of home NIV, and monitoring of patients established on home ventilation and describes technological advances in ventilation devices, interfaces, and monitoring to enhance comfort, promote long-term adherence, and optimise gas exchange.